Patterns of opioid prescribing for treating pain in patients with different age and gender: A retrospective cross sectional study - Zin, Che Suraya; Abdul Rahman, Norny Syafinaz; Ismail, Che Rokiah; Weng Cho, Leong (2015)
Introduction: Opioid utilization has been increasing over the last few decades and little is known about the patterns of opioid prescribing in different gender and age. Objective: To investigate patterns of opioid prescribing for pain treatment in patients with different age and gender. Method: This cross sectional study conducted at outpatient pharmacy Hospital Tengku Ampuan Afzan Kuantan (HTAA). Prescription records for four opioids (dihydrocodeine, fentanyl, morphine and oxycodone) issued between January 2013 and December 2014 were examined. Outcome measures included number of patients and prescriptions, age, gender and types of opioid. All analyses were performed using Stata 13 (Stata Corp LP, Texas, USA). Results: Overall, 270 patients were prescribed with opioid analgesics from 2013 to 2014. Of these, 121 (44.8%) were women and 149 (55.2%) were men. The predominant age groups for women and men were 51-65 and 66-80 years old respectively. During the same study period, 481(44%) prescriptions for opioid analgesics were prescribed for women while 612(56%) for men. Oxycodone was the most frequently prescribed in both women and men (39.5% vs. 38.6%) primarily for younger patients (<40years old), followed by morphine (38% vs. 28.1%), dihydrocodeine (15% vs. 20.2%) and fentanyl (7.48% vs.13.1%). Conclusion: Prescriptions for opioid analgesics were predominant in men compared to women primarily for age group 66-80 years old. Oxycodone was the most frequently prescribed in both genders mostly in the younger patients. Further research is required to explore the indication of opioid analgesics and its related clinical outcomes.